Rhinoplasty without nasal packing and splinting - Vulović Dejan; Kozarski Jevta; Radivojčević Uroš; Stepić Nenad; Milićević Saša; Petrović Nenad T. (Vojnosanitetski Pregled)
Background/Aim. Most surgeons, at the end of corrective rhinoplasty, use endonasal tamponade and external splinting, primarily because of hemostasis and immobilization. Possible complications of this surgery are various. Pain, nose edema, palpebral swelling and ecchymosis, are the most common and usual. The aim of our study was to evaluate the incidence of nonaesthetic complications and the efficiency of corrective rhinoplasty without the use of tamponade and external splint. Methods. One hundred and fiftyone patients, who underwent primary corrective rhinoplasty without endonasal tamponade and without an external splint, were analyzed at the Clinical Centre “Kragujevac” in Kragujevac, Serbia, in the period 1999–May 2016. The surgeries were done by the same surgeon. Instead of a splint, sterile skin adhesive tapes were used. Study was prospective, consecutive case-series type. We analyzed the possible complications and subjective estimates of the patients who underwent primary corrective rhinoplasty in described fashion. In assessing postoparative pain, the visual analogue scale (VAS) in a range of 1 to 5 was used. Palpebral swelling and ecchymosis, were estimated 24h after surgery, by the Surgeon Periorbital Rating of Edema and Ecchymosis (SPREE) scale ranging from 0 to 5. The degree of restriction of nasal respiration was evaluated by the scale 1–4. The overall comfort of patients in the postoperative period was evaluated according to a scale: good, no opinion, bad. The patient satisfaction with the aesthetic result was analyzed on 7th and 30th day after surgery, by a scale from 1 (very satisfied) to 5 (very dissatisfied). Results. There were 151 patients aged between 18–47 years. Females were more frequent (72.18%). Most of the patients (40.39%) had moderate pain. None of the patients had neither severe nor the worst pain and 59 patients had no pain at all. Eyelid edema and periorbital ecchymosis were moderate in all patients (100%). The other complications did not occur, apart from one (0.66%) unilateral epistaxis, on postoperative day 10. Most of the patients (52.97%), immediately after surgery, could freely breathe through the nose. The general impression of the patient comfort after surgery was mainly good (74.17%). The majority of patients (52.28%), were satisfied with aesthetic result after 7 days, and 52.32% after 1 month. There were very satisfied patients: on day 7 - 27.15% and on day 30 - 39.73%. Conclusion. We concluded that the rhinoplasty without using tamponade and immobilization was safe, comfortable and economical. The degree of pain, edema and ecchymosis were low, as well as the incidence of other complications.